Normalization of wave function of the band states - Okhunov, Abdurahim; Mamathonova, Gulbadanbegim Sh.; Hassan, Torla; Jahangir Alam, Mohammad; Ismoilov, Mukhtorjon X. (IIUM Press, 2015)

(untitled)
Low–lying band states are one of the most fundamental excitation modes in the energy spectra of deformed nuclei. This paper presents a theoretical analysis of the properties of a deformed nuclei within the phenomenological model [1]. The normalization of the wave functions of low –lying excited band states are also calculated.